Application of the Chinese Dunhuang algae well pattern in contemporary architecture design: a review paper - Liu, Hui; Liza Marziana Mohammad Noh,; Haslinda Abd Razak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to deeply analyze the symbolic meaning of the caisson patterns in the Mogao Grottoes in Dunhuang, China, and explore their innovative application potential in modern architectural design. As a unique carrier of culture and art aesthetics of Han and Tang dynasties, Dunhuang caisson pattern provides a valuable source of inspiration for modern architectural design with its rich symbolic elements and profound cultural connotation. This study uses the comprehensive research method of literature review, pattern semiotics and visual linguistics to systematically identify and deeply interpret the Dunhuang caisson patterns, revealing their profound integration with Han and Tang culture and artistic aesthetics. It is found that the symbolic elements of Dunhuang caisson pattern can be divided into two categories: natural elements and geometric elements. These elements not only have unique cultural connotations, but also inspire innovation in modern architectural design. The typical application cases of Dunhuang caisson pattern in modern architectural modeling design are collected, and the design effect is analyzed and evaluated in detail. The display of these cases provides a new way of thinking and practice for the integration of caisson pattern and contemporary aesthetics. The ultimate meaning of this study is to emphasize, protect and promote the Chinese Dunhuang caisson patterns. Through in-depth analysis, it can inject more cultural elements and innovative vitality into modern architectural design, and provide practical insights and new sources of inspiration for architectural project designers, which will help promote the innovative application and development of cultural heritage in contemporary society.